Comprehensive Scaling Analysis of Current Induced Switching in Magnetic Memories Based on In-Plane and Perpendicular Anisotropies - Jaiswal, Akhilesh (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2019)
10.1109/JETCAS.2016.2547698